2023
DOI: 10.55446/ije.2023.503
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Insecticides Against Rice White Backed Planthopper

Abstract: Efficacy of some insecticides (pymetrozine 50WG, sulfoxaflor 24SC and imidacloprid 17.8SL) was evaluated against rice white backed plant hopper (WBPH) Sogatella furcifera Horvath. Sulfoxaflor 24SC @218.7 g a.i./ ha and pymetrozine 50WG @ 187.5 g a.i./ ha gave significantly results (7.57 and 7.82/ hill, respectively).However, highest grain and straw yield (40.87 and 64.33 q/ ha) was observed with pymetrozine 50WG@ 187.5 g a.i./ ha and sulfoxaflor 24SC @ 218.7 g a.i./ ha (40.41 and 64.22 q/ ha). Regarding increm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…It has been observed that Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 9.38 kg ha -1 registered good yield, 4.81 t ha -1 and 4.72 t ha -1 which were on par with Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 7.50 kg ha -1 i.e., 4.79 t ha -1 and 4.70 t ha -1 in two consecutive seasons i.e., rabi, 2020-21 and kharif, 2021 respectively (Table 2 and 3). Thorat et al (2023) reported that the highest grain and straw yield (5.15 and 7.75 t ha -1 ) was recorded from the plot treated with chlorantraniliprole 18.5 SC, 30 g a.i. ha -1 .…”
Section: Efficacy Of Chlorantraniliprole 053%+fipronil 08% Gr Against...mentioning
confidence: 98%
“…It has been observed that Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 9.38 kg ha -1 registered good yield, 4.81 t ha -1 and 4.72 t ha -1 which were on par with Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 7.50 kg ha -1 i.e., 4.79 t ha -1 and 4.70 t ha -1 in two consecutive seasons i.e., rabi, 2020-21 and kharif, 2021 respectively (Table 2 and 3). Thorat et al (2023) reported that the highest grain and straw yield (5.15 and 7.75 t ha -1 ) was recorded from the plot treated with chlorantraniliprole 18.5 SC, 30 g a.i. ha -1 .…”
Section: Efficacy Of Chlorantraniliprole 053%+fipronil 08% Gr Against...mentioning
confidence: 98%